Life Cycle Ecological Footprint Reduction for a Tropical Building - Dilawar Husain; Ravi Prakash; Akbar Ahmad (Advances in Civil Engineering)
Rapid urbanization significantly impacts natural resource demands and waste management in the construction sector. In this study, a novel methodology has been developed that could assess the overall environmental impact of a building during its lifespan by considering resources such as building materials, energy use, emissions, water, manpower, and wastes. The proposed method can estimate the life cycle ecological footprint (EFT) of a building. The result indicates that 957.07 global hectares (gha) of bioproductive land are required during the lifespan of the case building. The CO2 absorption land is the most significant bioproductive land in the EFT of the building. The low environmental impact of building materials may reduce the ecological footprint (EF) of buildings, and using renewable energy can also reduce the operational EF of a building. The proposed building materials and solar PV systems have the potential to reduce the building’s life cycle environmental impact by up to two-thirds. The EF assessment of all existing and proposed buildings may be examined in order to execute strategies for a sustainable construction sector.